Design during COVID-19: Agents and allies in the role of designer, digital fabrication and distributed production - Herrera, P. C. (2021)
During COVID-19 global emergency, designers proposed solutions at different scales, as quick responses to demands from different agents. In the same way, we critically analyzed the emergence of allies, protocols and tools, which allowed the optimization of fabrication, from traditional manufacturing into distributed co-production. The analyzed local networks produced global co-design experiences, with involvement of FabLabs and users from different disciplines. Through case studies and the evaluation of surveys and testimonials from users and makers, we analyze the global panorama, to finally explore the specific situation in Latin America. This establishes a relationship between medical demand and digital fabrication, which allows evidence of positive and negative situations to be consider as new, significant aspects for the design in the future. The leading role acquired by the ecosystem surrounding digital fabrication during the pandemic, could enhance its processes in the search for greater positioning, changing society from within the different communities.